Performance assessment in archery: a systematic review - Vendrame, E.; Belluscio, V.; Truppa, L.; Rum, L.; Lazich, A.; Bergamini, E.; Mannini, A. (Sports Biomechanics, 2022)
Archery is a sport accessible to a wide range of people, no matter their age, gender or ability, and can be practiced both by able-bodied and impaired athletes on a level playing field. The recent increase in the number of studies concerning the biomechanical evaluation of the archery discipline revealed the need to advance an evidence-based approach for a standardised and objective assessment of the athletic gesture. A systematic literature search of relevant databases in July 2021 yielded 41 studies spanning 35 years (1986-2021). The research strings focused on the parameters, employed measurement systems and on the outcomes. The investigation of the influence of a wide range of physiological and kinematic parameters on the archer performance revealed that expert athletes tend to maximise postural stability and develop personal strategies of muscular activation and time management. These findings evidenced the importance of the repeatability of the technical gesture, opening additional scenarios for further investigations.